2013
DOI: 10.5713/ajas.2012.12478
|View full text |Cite
|
Sign up to set email alerts
|

Post-parturient Disorders and Backfat Loss in Tropical Sows in Relation to Backfat Thickness before Farrowing and Postpartum Intravenous Supportive Treatment

Abstract: The aim of the present study was to determine the evidence of post-parturient disorders and backfat loss during lactation in sows raised in tropical areas in relation to their backfat thickness before farrowing and postpartum intravenous supportive treatment. Backfat thickness was measured using A-mode ultrasonography at farrowing and weaning (25.5±1.4 d) in 70 sows. The sows were divided into three groups according to backfat thickness before farrowing, i.e., 15.0 to 20.0 mm (n = 21), 20.5 to 25.0 mm (n = 35)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…In accordance with previous reports [ 11 , 12 , 22 ], the amount of vaginal discharge positively correlated with the body temperature in sows. Physiologically, the body temperature increases and remains high during and after farrowing [ 23 ] due to nest-building activity, development of mammary glands and uterine contractions.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous reports [ 11 , 12 , 22 ], the amount of vaginal discharge positively correlated with the body temperature in sows. Physiologically, the body temperature increases and remains high during and after farrowing [ 23 ] due to nest-building activity, development of mammary glands and uterine contractions.…”
Section: Discussionsupporting
confidence: 93%
“…The reduced backfat loss indicated that sows in the IFI‐1.4 treatment used less body fat during lactation to supply the energy for maintenance requirement and milk production during lactation compared with those in the IFI‐0.7 treatment (Clowes, Aherne, Schaefer, Foxcroft, & Baracos, ; Kim, Yang, & Baidoo, ). The reduced backfat loss may help to maintain the reproductive performance of the post‐weaning sows (Tummaruk, ). In late lactation (days 13–18 and 19–24), feed intake was not affected by treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There is a link between variability in oocyte quality and developmental competence and asynchronous embryo development, which is a key factor determining embryo survival (184) . Even moderate feed restriction during lactation can lead to an accentuated loss of body fat and protein, which can result in reduced implantation sites and embryo viability at 35 d of the subsequent gestation (248) as well as decreased litter uniformity (34) . In Figs.…”
Section: Farrowing and Lactationmentioning
confidence: 99%
“…Roongsitthichai & Tummaruk (23) Gilts Rearing ≤17•0 ≥24•0 --Amdi et al (30) Gilts Mating ∼12•0 ∼19•0 Lower weight of piglets at birth, at weaning and at slaughter -Li et al (31) Sows (parity 3) Mating and farrowing -≥23•0 -Decreased litter size; lower piglet birth weight; higher rate of piglets born <0•9 kg; impaired placental efficiency; higher heterogeneity in piglets birth weight; increased oxidative stress and inflammation in placenta Cheng et al (12) Sows (multiparous) Late pregnancy and farrowing -≥21•0 -Lower piglets born alive and litter weight; exacerbated metabolic disorders in parturient sows and impaired piglets' intestinal health Zhou et al (32) Sows (parity Farrowing: ∼19•7 Tummaruk et al (34) Sows (multiparous) Farrowing 15•0-20•0 ≥25•0 -Decreased feed intake and higher backfat loss in lactation. Filha et al (35) Gilts Mating (36) Sows (parity 2-4) Late pregnancy ≥21•0 Increased piglets with low birth weight; impaired lipid metabolism and angiogenesis in placenta Farmer et al (24) Gilts Late pregnancy ≤15•0 ≥26•0 Impaired mammary development; lower litter weight gain during lactation Cools et al (37) Sows (multiparous) Late pregnancy ≤17•0 ≥23•0 Higher stillborn rate Higher stillborn rate; higher backfat loss in lactation Oliviero et al (8) Sows (multiparous) Late pregnancy and farrowing…”
mentioning
confidence: 99%